Climate change, Gender and Livelihoods Among Fisher communities in the Lake Victoria Zone Region in Kenya: Report of Proceedings of the Multi-stakeholder Technical Workshop - Adam, Rahma; Osano, Philip M.; Amwata, Dorothy; Lidigu, Leon; Ouko, Kevin; Ndiema, Nicholas (WorldFish, 2023)
This workshop report is about climate change, gender and livelihoods among fisher communities in the Lake Victoria Zone Region in Kenya. The purpose of the workshop was to share and validate the findings of the scoping study carried out by WorldFish from March to July, 2023. The objective of the study was to assess through a gender lens how climate change affects the fishing communities in two riparian counties, specifically in Homabay and Migori counties, which are located along Kenya’s Lake Victoria Zone Region.